Examining ROA, ROE, and FDR Contributions to CAR BSI During PostPandemic (2021-2023) - Kumaidi Kumaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to determine the effect of Return on Assets (ROA), Return on Equity (ROE), and Financing to Deposit Ratio (FDR) on financial performance, both simultaneously and partially, in relation to the Capital Adequacy Ratio (CAR). The research focuses on Bank BSI Syariah Indonesia, and the research sample is based on secondary data from annual reports released between 2021 and 2023. To analyze the data, this study uses SPSS 18. Several stages of analysis include conducting multiple linear regression tests, which encompass T and F hypothesis tests. The analysis results show that ROA has a significant positive effect on CAR, meaning that the higher the ROA, the greater the bank's capital adequacy. Conversely, ROE and FDR show a negative effect on CAR, as an increase in both variables is inversely related to CAR values. These findings provide valuable insights for bank management to improve financial performance and maintain capital stability. It is hoped that this research will contribute to the literature on Islamic finance and assist regulators in formulating policies that support the stability of the Syariah banking sector in Indonesia.